Science fiction and ELSI: three thoughts - Greely, Henry T. (Frontiers in Genetics, 2023)
Science fiction can be useful to those who analyze ethical, legal, and social issues in genetics, and the biosciences more broadly. It can provide examples of possible technological changes, occasionally valuable as predictions of the future but more often helpful as indicators of the likely social consequences of such technologies. This "what if" approach to science fiction can also provide a good pathway to exploring such issues. Science fiction can also allow a more distant, less realistic, and non-culture-specific context for exploring deep questions about humanity, ethics, and other major issues. At the same time, science fiction also has some negative effects on such analysis, or its reception as a result of the need for fiction to hold its audience by providing drama through conflict. This necessity for successful fiction often leads to technological or cultural changes being portrayed as catastrophic and dystopian, much more often than beneficial or utopian. This imbalance can predispose public opinion against innovations unfairly, in part by providing "examples" from fiction of similar innovations leading to bad outcomes. ELSI researchers should keep this fiction-induced bias in mind in their work.